¿Qué podemos aprovechar del análisis austiniano del significado y de la verdad? - Colomina Almiñana, Juan José (Logos. Anales del Seminario de Metafísica, 2010)
In last years, has gone becoming more radical increasingly a separation between the defenders of the semantic analysis of language (which think that the meaning of the utterance comes already inserted in the same words) and the supporters of a pragmatic vision of language (defenders of a meaning determined by contextual elements that allow to show what the speaker means). On the basis of establishing the origins of above mentioned separation, we show the first disputes among Austin and Strawson on meaning and truth (section 1). Also we will present the beginning of a dichotomy respect the determination of meaning (section 2): nowadays it is considered possible to differ between what is said and what is meant. We will defend the austinian point of view from the determination of meaning, beyond the speaker’ intention in language put from relief for Grice, who bets for a contextualist view of meaning (defending the necessity of external elements to the language to determine the meaning of linguistic utterances) that will have implications for Theory of Knowledge and Philosophy of Mind (section 3). In this paper, in addition, we try to defend a conception of the austinian philosophy that does justice to language and his nature, to meaning and his determination and to knowledge and his, trying to present, in turn, a particular theory of meaning according to the current polemics among literalists and contextualists.